Xylose from lignocellulosic waste in the production and industrial processing of pinneaple (Ananascomusus) - Ramírez Amador, Karla (2012)
Lignocellulosicwaste from the pineapple production is a raw material useful for the xylose production by hydrolysis and it can be converted to xylitol. The objective of this work was to study the hydrolysis of pineapple peel with sulfuric acid at variable concentration (2-6%), reaction time (0-350 min) and temperature at 98 ˚C. The concentration of xylose, glucose and degradation products as acetic acid and furfural was determined. Optimal conditions found for hydrolysis were 6% H2SO4 at 98 ˚C for 83 min which yield was 26,9 g xylose/L, 2,61 g glucose/L, 7,71 g acetic acid/L and 0,29 g furfural/L.